Juvenile Criminality in the Republic of Armenia (1993-2016 - Margaryan, A. (Bulletin of Yerevan University C: Jurisprudence, 2021)
Fight against crime is one of the most important, but at the same time the most challenging tasks of any state. According to RA official crime statistics, over the period of 1993-2016 the crime has increased for more than 1.4 time. However, the same trend can not be constated when looking over the development of juvenile crime, as the latter one has declined. The author has analysed the possible factors which braught to such a situation and came to the conclusion, that the decline of youth crime in the official statistics is a result of increased latency of the crimes committed by juveniles in parallel with the decrease of juveniles` proportion in the total population.
Keywords: juvenile crime, latency, structure of crime, situation of crime, registration of crimes, crime coefficient